Batch‐ and Continuous‐Flow Aerobic Oxidation of 14‐Hydroxy Opioids to 1, 3‐Oxazolidines—A Concise Synthesis of Noroxymorphone. Issue 30 (21st June 2016) - Gutmann, Bernhard; Weigl, Ulrich; Cox, D. Phillip; Kappe, C. Oliver
Abstract: 14‐Hydroxymorphinone is converted to noroxymorphone, the immediate precursor of important opioid antagonists, such as naltrexone and naloxone, in a three‐step reaction sequence. The initial oxidation of the N ‐methyl group in 14‐hydroxymorphinone with in situ generated colloidal palladium(0) as the catalyst and molecular oxygen as the terminal oxidant constitutes the key transformation in this new route. This oxidation results in the formation of an unexpected oxazolidine ring structure. Subsequent hydrolysis of the oxazolidine under reduced pressure followed by hydrogenation in a packed‐bed flow reactor using palladium(0) as the catalyst provides noroxymorphone in high purity and good overall yield. To overcome challenges associated with gas–liquid reactions with molecular oxygen, the key oxidation reaction was translated to a continuous‐flow process. Abstract : Aerobic C−H bond activation in flow : In only three steps 14‐hydroxymorphinone is transformed to noroxymorphone—the key precursor to valuable opioid antagonists and mixed agonists/antagonists. The novel process consumes only O2 and H2 as stoichiometric reagents and generates formaldehyde and water as the sole stoichiometric byproducts (see scheme).